2022
DOI: 10.3390/toxics10030144
|View full text |Cite
|
Sign up to set email alerts
|

Double-Sided Nano-ZnO: Superior Antibacterial Properties and Induced Hepatotoxicity in Zebrafish Embryos

Abstract: Zinc oxide nanoparticles (Nano-ZnO) have been widely used in the food, cosmetics, and biomedical fields due to their excellent antibacterial and antioxidant properties. However, with the widespread application of Nano-ZnO, Nano-ZnO inevitably enters the environment and living organisms, causing harm to human health and ecosystem safety. Therefore, the biosafety and toxicological issues of Nano-ZnO are gradually being emphasized. Our study found that Nano-ZnO has superior antibacterial properties compared to of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…Like other metal oxides, zinc oxide can change its physicochemical characteristics under the influence of the environment, and, unfortunately depending on its concentration, ZnO can be hazardous to the life of living organisms and ecosystem safety. Therefore, special attention is paid to the control of the release of toxic zinc ions from the solution, especially in vivo studies 25 , 26 . Lee et al 27 showed that the toxicity of ZnO NPs can be correlated well with the zinc concentration and through transformation thought interaction ZnO with sulphur, phosphate, and ferric oxide.…”
Section: Introductionmentioning
confidence: 99%
“…Like other metal oxides, zinc oxide can change its physicochemical characteristics under the influence of the environment, and, unfortunately depending on its concentration, ZnO can be hazardous to the life of living organisms and ecosystem safety. Therefore, special attention is paid to the control of the release of toxic zinc ions from the solution, especially in vivo studies 25 , 26 . Lee et al 27 showed that the toxicity of ZnO NPs can be correlated well with the zinc concentration and through transformation thought interaction ZnO with sulphur, phosphate, and ferric oxide.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, ZnO-NPs were reported to damage the hepatic tissue as evidenced by elevated liver enzyme markers in the serum of Oreochromis niloticus and C. carpio [ 20 , 21 , 24 ] and decreased serum albumin and total protein [ 21 ]. The induced structural changes in the liver of ZnO-NPs-exposed fishes could be attributed to hepatic oxidative damage with an increased rate of lipid peroxidation and suppression of antioxidant enzymes [ 11 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it increased the triglyceride contents and the activity of the lipogenic enzymes besides the upregulation of the lipogenic genes including 6pgd , fas , and srebp1 , and the downregulation of small heterodimer partner ( shp ) and farnesoid X receptor ( fxr ). In addition, He et al recorded hepatic steatosis in ZnONPs-treated zebrafish [ 11 ]. Collectively, this could result from the promotion of fatty acid synthesis via activation of the srebp gene and its downstream genes fasn and acc1 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zinc oxide NPs (ZnO-NPs) are widely used in the biomedical field and have been extensively applied for antibacterial (Singh, Sharma et al, 2021). It was found that the antibacterial activity of ZnO-NPs against Escherichia coli and Staphylococcus aureus was similar to that of levofloxacin, a commonly used broadspectrum antibiotic (He, Li et al, 2022). ZnO-NPs are considerable antibacterial agents for contact lenses to reduce the risk of infection from wear (Shayani Rad, Sabeti et al, 2020).…”
Section: Antibiotic Action (Microbial-related Eye Diseases)mentioning
confidence: 99%